Autophagy and pancreatitis - Gukovskaya, Anna S. (American Physiological Society, 2012)
Acute pancreatitis is an inflammatory disease of the exocrine pancreas that carries considerable morbidity and mortality; its pathophysiology remains poorly understood. Recent findings from experimental models and genetically altered mice summarized in this review reveal that autophagy, the principal cellular degradative pathway, is impaired in pancreatitis and that one cause of autophagy impairment is defective function of lysosomes. We propose that the lysosomal/autophagic dysfunction is a key initiating event in pancreatitis and a converging point of multiple deranged pathways. There is strong evidence supporting this hypothesis. Investigation of autophagy in pancreatitis has just started, and many questions about the “upstream” mechanisms mediating the lysosomal/autophagic dysfunction and the “downstream” links to pancreatitis pathologies need to be explored. Answers to these questions should provide insight into novel molecular targets and therapeutic strategies for treatment of pancreatitis.